The SDG agenda and university transformation in Africa: The decolonial turn deferred? - Shireen Motala; Yusuf YM Sayed; Terri Maggott (African Journal of Teacher Education, 2023)
The Sustainable Development Goals (SDGs) agreed in September 2015 set the scene for a renewed and ambitious development framework in a global context of widening inequalities within and between countries, global economic crises, conflict and climate change. Higher education is framed in several of the targets that make up SDG 4 and is also argued as central to achieving all 17 goals. However, the extent to which they engage with higher education in the context of calls for responsive, decolonised higher education remains underexplored. It is this gap that this paper addresses, arguing that while the SDGs take a broad approach to education the focus on specific targets and indicators limit states’ autonomy by de-territorialising local frameworks (Sayed & Moriarty, 2020). As a result, universities in Africa struggle to assert their agendas as power is overly located at the supra national level. We use the case of South African higher education to examine how and in what ways the national education agenda articulates with the SDG agenda. In particular, we focus on the lack of a clear equity and anti-racist focus in the SDG agenda which fails to engage with the disciplinary hold of racism over knowledge. We use Boaventura de Sousa Santos’ (2014) notion of difficult questions in higher education with weak answers to address what a decolonised and deracialised higher education system might look like. In particular, we articulate how Western domination has marginalised knowledge present in the global South. In so doing, we describe the influence of the SDGs in higher education noting the strides made but also their limited application in the global South and the decolonial turn. We argue that the decolonisation of knowledge in higher education is a collective process in which disruptive disciplinary practices contribute to cognitive global justice.